2011
DOI: 10.1002/jts.20662
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on traumatic grief treatment program for Japanese women bereaved by violent death

Abstract: This pilot study aimed to refine a treatment approach for traumatic grief due to violent loss. Our Traumatic Grief Treatment Program, a modification of Shear's complicated grief treatment (Shear et al., 2005), comprises psychoeducation, in vivo exposure, imaginal exposure, discussion of memories about and imaginal conversation with the deceased. Thirteen of 15 Japanese women suffering from posttraumatic stress disorder (PTSD) due to traumatic grief completed 12 to 16 weekly individual sessions based on their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…In a smaller study conducted at multiple sites, Boelen et al (63) reported similar findings, comparing Cognitive Behavioral Treatment (CBT) with supportive counseling for CG and found a significant reduction in CG symptoms and general psychopathology in the CBT group compared to supportive counseling. A number of small studies using a similar intervention have now been published, including Acierno et al (64), Asukai et al (65), Rosner et al (66), Papa et al (67) and Supiano and Luptak (68). Wagner et al (69) tested the effectiveness of an internet-based cognitive behavioral therapy for CG.…”
Section: Complicated Grief Treatmentmentioning
confidence: 99%
“…In a smaller study conducted at multiple sites, Boelen et al (63) reported similar findings, comparing Cognitive Behavioral Treatment (CBT) with supportive counseling for CG and found a significant reduction in CG symptoms and general psychopathology in the CBT group compared to supportive counseling. A number of small studies using a similar intervention have now been published, including Acierno et al (64), Asukai et al (65), Rosner et al (66), Papa et al (67) and Supiano and Luptak (68). Wagner et al (69) tested the effectiveness of an internet-based cognitive behavioral therapy for CG.…”
Section: Complicated Grief Treatmentmentioning
confidence: 99%
“…Different studies report effects of interventions for homicidally bereaved individuals with elevated symptoms of psychopathology, such as holistic retreat sessions (Tuck, Baliko, Schubert, & Anderson, ), grief treatment programs (Asukai, Tsuruta, & Saito, ), and restorative retelling (Saindon et al, ). Rynearson () provided group psychotherapy, which focused on dysfunctional affects following homicidal loss and (re)building resilient coping responses.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic grief may be an important psychodynamic contributor to PTSD symptoms [5], which is quite evident in the tiger-widow case (Case 5) here. The trauma scenario she described is horrific, devastating and had a significant impact on her grief and bereavement process.…”
Section: Discussionmentioning
confidence: 63%